O comportamento ansioso a a memória espacial são capazes de predizer a capacidade natural de adaptação as marcha em camundongos? um estudo exploratório - Schiavo, Aniuska (2021)
Adapt walking to different environmental contexts is a critical sensorimotor skill for functional locomotion. This study aims to study the natural variability of the ability to adapt walking in Balb/cJ mice, as well as the predictive capacity of spatial memory and anxiety-like behavior metrics on the performance of walking adaptability. We used 60 adult mice (males n = 28 and females n = 32) and a battery of behavioral tests that aimed to assess general locomotor exploration levels (Open Field), anxiety-like behavior (Elevated Plus Maze), spatial memory (Y-Maze and Barnes Maze) and walking adaptability (Ladder Rung Walking Test - LRWT). This study is part of a project approved by the Ethics Committee on Animal Use at PUCRS (8955). The animals were divided into three groups, based on their LRWT performance: superior (SP, percentiles ≥ 75), regular (RP, percentiles 74 to 26) and inferior (IP, percentiles ≤ 25) performers. Data normality was assessed by the Kolmogorov-Smirnov test. Parametric data were analyzed by one-way ANOVA and Tukey's post-hoc. Kruskal-Wallis and Mann-Whitney tests were used for comparisons between groups for non-parametric variables. Potential correlations were studied using the Spearman test. We compared females and males and no significant differences were found in the behavioral tests. A significant difference was observed regarding the exploration time in the EPM closed arms. Animals from the SP and IP groups spent more time in these arms compared to the RP group, while no difference was observed between the SP and IP groups. A between-group trend towards significance was observed in the Y-Maze. No between-group differences were found in the Open Field and Barnes Maze tests. The Poisson regressions revealed that with every second spent in the EPM closed arms, the probability of the animal exhibiting extreme percentiles in the LRWT increased by 0.3%. Moreover, those that spent 219 seconds or more in those arms were 39% more likely to exhibit extreme walking performance. It is suggested, therefore, that an anxiety-like behavioral trait has a dual effect on the ability to adapt to walk. Further studies are needed to better understand how cognitive-motor mechanisms interact with the normal range of anxiety to influence success in adapting walking.